Loss Of Platelet Membrane Glycoproteins Or Terminal Sialic Acid Detected By Fitc-Lectins - McGregor, L; McGregor, J L; Clemetson, K J; Dechavanne, M; Lüscher, E F (Thrombosis and Haemostasis, 1981)
Pre-thrombic conditions in certain individuals resulting from enhanced platelet-vessel wall or platelet-platelet interactions are perhaps characterized by a reduction in certain membrane glycoproteins or loss of terminal sialic acid. In order to investigate if such changes are detectable, the binding of FITC-lectins to human platelets treated under in vitro conditions with certain proteases to mimic possible in vivo changes occuring on the platelet surface, has been examined. Human platelets were isolated, washed and either treated with neuraminidase (10 U) or plasmin (1 CU) before fixing with formaldehyde. Binding studies were performed by the method of Monsigny et al. using FITC labelled wheat germ agglutinin (WGA), Lens culinaris lectin (LCL), Ricinus communis agglutinin (RCA) and concanavalin A (ConA). The number of lectin-binding sites (n) and the dissociation constant (Kd) were obtained by Steck and Wallach reciprocal plots. After neuraminidase or plasmin treatment n was reduced but Kd remained approximately the same with WGA. FITC-RCA-60 gave a slight fluorescence with untreated and very strong fluorescence with neuraminidase treated platelets. Platelet glycoproteins separated by 2-dimensional gel electrophoresis were identified by binding of fluorescent lectins. Plasmin decreased the intensity of GP Ib and IIb and removed Ia completely. Neuraminidase decreased the labelling of Ib by WGA. These techniques show promise as methods of detecting pre-thrombotic conditions.